2021
DOI: 10.3390/su13063406
|View full text |Cite
|
Sign up to set email alerts
|

Applying Social Learning to Climate Communications—Visualising ‘People Like Me’ in Air Pollution and Climate Change Data

Abstract: Technological approaches to carbon emission and air pollution data modelling consider where the issues are located and what is creating emissions. This paper argues that more focus should be paid to people—the drivers of vehicles or households burning fossil fuels (‘Who’) and the reasons for doing so at those times (‘Why’). We applied insights from social psychology (social identity theory and social cognitive theory) to better understand and communicate how people’s everyday activities are a cause of climate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…5) Logistics: Bring individuals from a neighbourhood together online during the project to find common ground and work together. Grounded in social identity (Tajfel, 1974) and social cognitive/learning theory (Cialdini et al, 1990), norm setting and seeing 'people like me' in citizen science projects can motivate and inspire (Fogg-Rogers et al, 2021). 6) Logistics: Make the live online environment intimate, for example, split participants into smaller groups/rooms during online sessions to allow everyone the chance to talk and share their thoughts; make space and time to get to know one another; break the ice.…”
Section: Reflections and Conclusionmentioning
confidence: 99%
“…5) Logistics: Bring individuals from a neighbourhood together online during the project to find common ground and work together. Grounded in social identity (Tajfel, 1974) and social cognitive/learning theory (Cialdini et al, 1990), norm setting and seeing 'people like me' in citizen science projects can motivate and inspire (Fogg-Rogers et al, 2021). 6) Logistics: Make the live online environment intimate, for example, split participants into smaller groups/rooms during online sessions to allow everyone the chance to talk and share their thoughts; make space and time to get to know one another; break the ice.…”
Section: Reflections and Conclusionmentioning
confidence: 99%
“…When the visual distance is generally around 10 m, the speed of motor vehicles should be controlled below 5 km per hour [3]. Owing to severe air pollution, which can reduce travel visibility and result in varying degrees of traffic congestion, some private car owners choose public transportation [6]. Therefore, air pollution may reduce residents' willingness to travel and affect their choice of transportation; its mechanism of action is multifaceted [7].…”
Section: Introductionmentioning
confidence: 99%
“…Initially, research on climate change communication focused on how to accurately present the science that validated the existence and impact of climate change on individual-level behaviors. For example, a study in Northern Canada found that talking with family and friends about climate change was associated with a measure of individual-level climate change behaviors, such as recycling and reducing beef consumption [6]. However, to increase the probability that climate change communication will lead to actions, communication about climate change needs to provide information about the actions necessary to address it, as well as encourage, support, and symbolically reward activism [7,8].…”
Section: Introductionmentioning
confidence: 99%